2011
DOI: 10.1007/s00592-011-0299-4
|View full text |Cite
|
Sign up to set email alerts
|

The carriage of risk variants of CDKAL1 impairs beta-cell function in both diabetic and non-diabetic patients and reduces response to non-sulfonylurea and sulfonylurea agonists of the pancreatic KATP channel

Abstract: On chromosome 6q22.3, a cluster of single-nucleotide polymorphisms located in intron 5 of the cyclin-dependent kinase 5 (CDK5) regulatory subunit-associated protein 1-like 1 (CDKAL1) gene were shown to confer susceptibility to type 2 diabetes in multiple ethnic groups. The diabetogenic role of CDKAL1 variants is suggested to consist in lower insulin secretion probably due to the insufficient inhibition of the CDK5 activity. In this study, we assessed the association of several SNPs of CDKAL1 with T2D in 772 Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 45 publications
3
29
2
3
Order By: Relevance
“…Two studies deviating from the Hardy-Weinberg equilibrium (HWE) were rejected. All of information was extracted from 26,120 T2DM cases and 36,447 controls (Table 1)69101112131415161718192021. One publication generally included one study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies deviating from the Hardy-Weinberg equilibrium (HWE) were rejected. All of information was extracted from 26,120 T2DM cases and 36,447 controls (Table 1)69101112131415161718192021. One publication generally included one study.…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, Chistiakov et al found that the allele G of rs7756992 with higher diabetes risk thereby replicating the predisposing role of CDKAL1 gene in etiology of T2DM in a Russian population (OR = 1.21, 95% CI: 1.04–1.42, P = 0.017)9. In 2013, Li W et al found the similar result in a Chinese population (OR = 1.50, 95% CI: 1.11–2.04, P = 0.009)10.…”
mentioning
confidence: 94%
“…CDKAL1 has been shown to function as a tRNA modification enzyme, and its activity is associated with ATP generation and first-phase insulin secretion [40], [41], [42]. The carriage of CDKAL1 risk variants may lead to lower insulin release and impaired conversion of proinsulin to insulin in pancreatic beta cells [43], [44], [45]. Although the effect of derived rs9368197 allele on glucose-induced insulin response is similar to that reported for the derived rs7754840 allele, the finding that the derived rs7754840 allele (i.e., C) is associated with an elevated GIP response is unique because the same allele has been found to be associated with type 2 diabetes and reduced insulin secretion in earlier studies [43], [44], [45], [46].…”
Section: Discussionmentioning
confidence: 99%
“…The carriage of CDKAL1 risk variants may lead to lower insulin release and impaired conversion of proinsulin to insulin in pancreatic beta cells [43], [44], [45]. Although the effect of derived rs9368197 allele on glucose-induced insulin response is similar to that reported for the derived rs7754840 allele, the finding that the derived rs7754840 allele (i.e., C) is associated with an elevated GIP response is unique because the same allele has been found to be associated with type 2 diabetes and reduced insulin secretion in earlier studies [43], [44], [45], [46]. These results suggest that the selection of derived rs7754840 allele has opposite effects on insulin secretion and glucose-induced GIP response.…”
Section: Discussionmentioning
confidence: 99%
“…Although CDKAL1 is associated with T2DM and obesity in East‐Asians, there are relatively few published reports that have assessed the role of this gene in the pathogenesis of diseases in Chinese populations. The rs10946398 single nucleotide polymorphism (SNP), one of the strongest associations with diabetes among all known SNPs analysed to date, has received less attention than rs7754840 or rs7756992 . The aim of this study was to investigate the impact of the rs10946398 SNP of CDKAL1 on insulin secretion, insulin resistance and quantitative glucose‐related traits in a Chinese population.…”
Section: Introductionmentioning
confidence: 99%